The day Jimmy$1 (Bs boa ate the wash s - Noble, Trinka Hakes; Kellogg, Steven (New York : Dial Press, 1980)
Jimmy$1 (Bs boa constrictor wreaks havoc on the class trip to a farm.s
Keywords: Boa constrictor -- Fiction; Snakes as pets -- Fiction; Farms -- Fiction; Schools -- Fiction